Electronic band structure of highly mismatched GaN1−xSbx alloys in a broad composition range - Segercrantz, N.; Yu, K.M.; Ting, M.; Sarney, W.L.; Svensson, S.P.; Novikov, S.V.; Foxon, C.T.; Walukiewicz, W. (American Institute of Physics, 2015)
In this letter, we study the optical properties of GaN1xSbx thin films. Films with an Sb fraction up to 42% were synthesized by alternating GaN-GaSb layers at a constant temperature of 325 C. The measured optical absorption data of the films are interpreted using a modified band anticrossing model that is applicable to highly mismatched alloys such as GaN1xSbx in the entire composition range. The presented model allows us to more accurately determine the band gap as well as the band edges over the entire composition range thereby providing means for determining the composition for, e.g., efficient spontaneous photoelectrochemical cell applications